Konstruksi Dar’u al-Mafasid dalam Putusan Hakim pada Perkara Perceraian Akibat Perselisihan Terus Menerus - Ahmad Ihksaludin; Yudi Wahyudin; Mumu Fahmudin; Abdul Kodir Alhamdani; Mohammad Husni Mubarok (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2025)
The high rate of divorce due to continuous disputes in Religious Courts has prompted judges to use the jurisprudential maxim dar'u al-mafasid muqaddamun 'ala jalb al-mashalih as the normative basis for their legal considerations. However, the application of this maxim in judicial practice is often carried out disproportionately and without measurable standards, potentially producing decisions that are inconsistent with the objectives of Islamic law. This study aims to analyze the construction of the dar'u al-mafasid maxim in judges' decisions on divorce cases due to continuous disputes, evaluate its proportionality from the perspective of maqasid al-syari'ah, identify its construction patterns, and formulate an ideal and measurable construction model. This research employs a normative legal research method with statutory, conceptual, case, and philosophical-hermeneutic approaches. Legal materials were collected through documentation studies and analyzed qualitatively using content analysis, descriptive-analytical, comparative, and normative-evaluative techniques. The findings reveal that the construction of the dar'u al-mafasid maxim in judges' decisions is built through three stages: identification of mafsadat and maslahat, weighing (muwazanah) between them, and establishing priorities (awlawiyat); however, significant inconsistencies and disproportionality exist across various court levels. Three construction patterns were identified: fact-based, irreconcilability-based, and maqasid al-syari'ah-based. This study formulates an ideal construction model through five integrative stages: comprehensive fact verification, optimal reconciliation efforts, measurable mafsadat identification and assessment, proportional weighing integrating four dimensions of moderate jurisprudence, and maqasid al-syari'ah-based decision-making. This model is expected to serve as a guideline for Religious Court judges in producing substantively just decisions aligned with the objectives of Islamic law.